Alternative Thawing Methods for the Blanched/Non‐Blanched Potato Cubes: Microwave, Ohmic, and Carbon Fiber Plate Assisted Cabin Thawing. Issue 2 (5th May 2016) - Icier, Filiz; Cokgezme, Omer Faruk; Sabanci, Serdal
Abstract: The effects of conventional‐C, carbon fiber plate assisted cabinet heater‐CPAC, ohmic‐OT, and microwave thawing‐MT techniques on changes of some quality characteristics and resistant starch (RS) content of potato ( Solanum tuberosum L.) cubes (18 × 18 × 18 mm) were investigated. The effects of blanching prior to the freezing on thawing characteristics were also determined. The thawing times of non‐blanched samples were determined as 23, 580 ± 485 s, 5360 ± 40 s, 205 ± 18.25 s and 19.26 ± 1.49 s for conventional, CPAC, OT, and MT methods, respectively. The blanching process increased the thawing times in general. OT and CPAC thawing methods served lower RS content for thawed potato samples. The potato cubes thawed by OT and MT were softer than C and CPAC thawed potato cubes ( P  < 0.05). The highest color change was found for MT of blanched samples and conventional thawing of non‐blanched samples. The electrical methods could be alternative thawing methods in terms of providing shorter thawing times and desirable changes on some quality characteristics. Practical Applications: The conventional thawing of high amount of frozen food products have posed a problem for catering industry. The long thawing time, drip loss issues, quality loses and possible microbial spoilage are lacks of conventional thawing method. The electroheating methods such as ohmic, microwave and unique carbon fiber plate assisted cabinet heating were employed as alternative thawing techniques. Thawing time of potato cubes were shortened and quality characteristics, such as drip loss, texture profile, color properties and resistant starch (RS), were improved by novel thawing methods. The obtained results reveal that the application of alternative thawing methods may lead to decreasing of the operating cost due to shorter process time and minimizing the changes in color, texture and nutritional compounds.